Osmanlı arşiv belgelerine göre işgal döneminde İstanbul (16 Mart 1920-31 Aralık 1922) - Afyoncu, Fatma (My University, 2009)
The topic of this research is the analysis of the period of Istanbul’s official occupation immediately after the Mondros Armistice during 16 March 1920 and 31 December 1922, according to the Ottoman Archive documents. İstanbul, the long term capital of Ottomans, was occupied after the First World War. The sorrow days of the capital city would take five years, from the de facto invasion date, namely 13 November 1918, up to 31 December 1922. During the occupation, Britain was not only the most effective one in Istanbul between the Entente States, but also the most insistent state for the official invasion of the city. However, Greeks were the most brutal for Istanbul’s Muslim population with Greek inhabitants of the city. The French and Italians, on the other hand, in order to prevent the British dominion in the city, behaved parallel to them and victimazed the residents. People of Istanbul, lived with public order problems during the occupation and many public and private buildings were confiscated. Not only life and property safety got lost, but also religious and national feelings of the Turkish nation were hurt. Prisoners were evacuated by the occupying forces. Due to food scarcity, the expensiveness, unemployment and the other issues such as unpaid wages, livelihood distress emerged. Moreover, the social life was turned upside down by the continuous fires which victimised many people, immigrants coming from different parts of Anatolia and refugees from Russia.
Keywords: Arşivler_Osmanlı İmparatorluğu, 1299-1918; İstanbul_Tarih; İşgaller, İstanbul_Şehirler ve Bölgeler